Argentina's distributional failure: the role of integration and public policies - Gasparini, Leonardo Carlos (2004)
This paper scrutinizes income distribution changes in Argentina, stressing the links between the process of integration to the world economy and the growth of inequality and poverty. The study presents alternative explanations of the distributional patterns observed in Argentina and assesses their relative importance in the light of the economic theory and the available empirical evidence. The paper argues that although integration may certainly increase inequality in the short and medium run for countries like Argentina, the government can smooth the transition. Failing to do that, as in the Argentine case, may place the whole process of integration and liberalization into doubt and risk.